Some Things Don’t Age Well: How the Legacy of Prohibition Hurts Consumers and Small Businesses in the Modern Alcohol Industry - Colby Groom (Washington University Journal of Law and Policy, 2026)
The United States alcohol industry, its production, distribution, and consumption, lies below one of the most complex regulatory structures in the nation, which has diminished competition, undermined small businesses, and diluted consumer buying power. Although the Prohibition era’s ban on alcohol distribution and production is a thing of the past, the legal ramifications of its repeal exists today. States have the power to regulate the sale of alcohol in their jurisdiction, with states adopting a three-tier structure to regulate the industry: the tiers separate production and retail by requiring that beverage alcohol be sold through a distributor, effectively forbidding businesses licensed in one tier from operating or holding financial stakes in another. The effect is an industry that still feels the purposes of Prohibition today; temperance movements created restraints on the system, states can more easily tax alcohol at a higher rate, and economic power is taken from small and mid-sized producers. As a result of the three-tier system, anti-competitiveness between the large businesses festers, consumer prices increase, and local alcohol producers and distributors are inhibited from growing. This Note describes the changing American drinking culture and the underlying role that the federal government played in shaping the alcohol industry before, during, and after Prohibition. Where the growth of the domestic industry led to overconsumption of alcohol and underscored the impetus for the temperance movement and Prohibition, the hasty passage of the Eighteenth Amendment and its rapid repeal in the Twenty-First Amendment has laid the foundation for the current misconceived regulatory structure of the alcohol industry today. Instead of diluting the power of businesses and consumers alike through the three-tiered structure that post-dates Prohibition, the federal government should adopt a standardized system through the Spending Clause where consumers experience a variety of alcohol to choose from and producers, wholesalers, and retailers experience reduced market barriers to grow their businesses. Specifically, allowing a direct small producer-to-retailer sales route and taxing it to correspond with wholesaler markups would be beneficial to the industry and consumer. As the beverage alcohol industry continues to feel the effects of Prohibition and the temperance movement, the regulatory structure of this industry should favor small businesses, local producers, wholesalers, and consumers that make the backbone of this industry.
Keywords: #AlcoholRegulation; #ProhibitionLegacy; #TwentyFirstAmendment; #EighteenthAmendment; #TemperanceToTaxation; #CraftProducerRights; #SpendingClauseReform; #BeerWineSpiritsPolicy; #SmallBusinessAlcohol; #ModernizeAlcoholLaws